The 2-Adic Valuation of the Cardinality of Jacobians of Genus 2 Curves over Quadratic Towers of Finite Fields - Theriault, N (World Scientific Publishing Co. Pte Ltd, 2019)
Given a genus 2 curve C defined over a finite field q of odd characteristic such that 2|#Jac(C)(q), we study the growth of the 2-adic valuation of the cardinality of the Jacobian over a tower of quadratic extensions of q. In the cases of simpler regularity, we determine the exponents of the 2-Sylow subgroup of Jac(C)(q2k). © 2019 World Scientific Publishing Company.